The gut–liver axis in immune remodeling of hepatic cirrhosis - Guan, Huayu; Zhang, Xiang; Kuang, Ming; Yu, Jun (Frontiers in Immunology, 2022)
Gut-liver axis allows host-microbiota communications and mediates immune homeostasis through bidirectional regulations in healthy settings. Whereas in diseases, gut dysbiosis along with impaired intestinal barrier will introduce pathogens and their toxic metabolites into the system, causing massive immune alternations in the liver and other extrahepatic organs. Accumulating evidences suggest that these immune changes are associated with the progression of many liver diseases, especially hepatic cirrhosis. Pathogen-associated molecular patterns originated from gut microbes directly stimulate hepatocytes and liver immune cells through different pattern recognition receptors, a process further facilitated by damage-associated molecular patterns released from injured hepatocytes. Hepatic stellate cells, along with other immune cells, contribute to this proinflammatory and profibrogenic transformation. Moreover, cirrhosis-associated immune dysfunction, an imbalanced immune status featured by systemic inflammation and immune deficiency, is linked to gut dysbiosis. Though the systemic inflammation hypothesis starts to link gut dysbiosis to decompensated cirrhosis in a clinical perspective, a clearer demonstration is still needed for the role of gut-liver-immune axis in cirrhosis progression. This review is to discuss the different immune states of gut-liver axis in both healthy and cirrhotic settings and more importantly, to summarize the current evidences about how microbiota-derived immune remodeling contributes to the progression of hepatic cirrhosis via the gut-liver axis.